The Impact of Work Stress on Employee Mental Health and Productivity - Ahmad Agustiadi; Raesti Lim Halima (SEED: Journal of Scientific Research, 2026)
This research aims to analyze the effect of work stress on the mental health and productivity of employees in a modern work environment. Job stress caused by work demands, conflicts between co-workers, time pressure, and imbalance between work and personal life have become significant problems that impact individual well-being. The research method used was a quantitative approach with a survey of 150 employees in the industrial and service sectors. Data was collected using a structured questionnaire and analyzed using linear regression to identify the relationship between work stress variables, mental health and productivity. The research results show that work stress has a significant negative influence on employee mental health, which is characterized by increased levels of anxiety, depression and emotional exhaustion. In addition, it was found that decreased mental health due to work stress contributed to decreased employee productivity. These findings emphasize the importance of implementing workplace stress management strategies, such as employee wellness programs, work flexibility, and time management training to improve work-life balance. Thus, this research provides a practical contribution in designing organizational policies that support employee well-being and performance.